A phase-based nutritional recovery model: Integrating metabolism, allostatic load, and nutrient timing in athletic performance and revocery - Georgescu, A. D.; Georgescu, A. A.; Lica, P. M. A.; Radu, L. E.; Popovici, I. M.; Rohozneanu, M. D.; Popa, C.; Cazan, F.; Gidu, D. V.; Popa, C. (Science, Movement & Health, 2026)
Aim. The present research aims to analyze the role of nutrition as a fundamental component in physical performance and functional recovery following physical effort, addressing the need for a clearer integration of nutritional principles into recovery processes.